Effect of Fluctuating Load on Fatigue of PPCW Flat Wagon - Teguh Suprianto; Achmad Syaifudin; Lanang Wahyu Pamungkas; Julendra Bambang Ariatedja; Abdul Rohman Farid (JMES The International Journal of Mechanical Engineering and Sciences, 2023)
Flat wagons are logistic railway vehicles that are always subjected to a heavy dynamic load. One type is the 42 ton flat wagon developed by INKA Ltd., which is well known as PPCW flat wagon. The initial design of this flat wagon was operated using a container. Nevertheless, it can operate safely without a container as well. This study was conducted to mitigate the effect of fluctuating load on fatigue of 42 ton flat wagons as cement carriers, with or without a container. The 3D flat wagon model was built and exported to ANSYS Workbench 19 to simulate the effect of the variable and mean stresses generated within the wagon. Several operational modes were applied to the model, such as an accelerated condition of 0.21 m/s2, a constant straight track, a turn uphill track, an inclined track, a turn downward track, and a decelerated condition of 0.3 m/s2. Transient structural, static structural, and modal analysis types are applied in the simulation consecutively to adapt the track variations. Due to the loading being dominated by compressive load, a negative stress ratio of 1.5 was utilized as the stress ratio of alternating stresses. The numerical study indicated that the straight, turn uphill, and turn downward tracks could exaggerate the stress generated due to dynamic loading. Potential fatigue failure could occur because the dynamic load produced fluctuating stresses, either alternating or mean stresses, that could damage the structural integrity of the flat wagon.